Analysis of Sectoral Features in Hungarian Accredited Innovation Clusters - Petruska, Ildikó; Kovács, István (Theory, Methodology, Practice – Review of Business and Management, 2016)
This paper discusses how sectoral characteristics are reflected in the operation of Hungarian accredited innovation clusters. The purpose of this paper is to analyse how sectoral bonding affects the mission of the clusters as well as their innovation and market goals, the membership criteria of the management and the motivation of the members and their cooperation. The study uses a literature review and in-depth interviews to identify the interrelations and the differences between networks and clusters, and to observe several sectoral features in the Hungarian accredited innovation clusters.